Preservation of Sasoki Dance Culture for Youth in Tihulale Village, West Seram Regency - Junita Liliana Kundre; Grace Silon Waitrata (Peneliti.net, 2022)
This study aims to determine whether there is a cultural preservation of Sasoki dances for young people in Tihulale Village, West Seram Regency. This study uses a qualitative approach, to describe the symptoms that arise in the process of preserving the Sasoki dance culture for young people. The results of the study show that culture is a very important thing and cannot be separated from our lives. However, along with the changing times and technological advances that are increasingly widespread among the community, many cultures have been eliminated. Likewise with Sasoki culture which has now disappeared but because Sasoki is considered to have its own meaning for the people of Tihulale Country, Sasoki is made into a dance and taught to the younger generation so that it does not just disappear.